2020
DOI: 10.1002/admi.202000154
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy of Constructing a Highly Fluorinated Solid‐Electrolyte Interface towards High‐Performance Lithium Anode

Abstract: Lithium fluoride (LiF)‐rich solid‐electrolyte interface (SEI) layers are reported as an effective method to suppress lithium dendrites growth and capacity fading for Li‐plating/Li‐stripping. Herein, a new pre‐fluorination strategy is proposed by constructing an MgF2 thin film on pristine copper foil via the magnetron sputtering. This MgF2 film proves a lithiophilic substrate and shows highly irreversible conversion reaction to LiF in the first cycle. The resulting uniform LiF‐rich dual‐layered SEI layer helps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A similar strategy via the MS deposition of MgF 2 was also adopted by Li et al. ( 127 ). The MgF 2 layer was served as a lithiophilic substrate to form a uniform LiF-Mg dual-layered SEI through its irreversible conversion reaction with Li metal.…”
Section: Surface Preteatment Strategiesmentioning
confidence: 99%
“…A similar strategy via the MS deposition of MgF 2 was also adopted by Li et al. ( 127 ). The MgF 2 layer was served as a lithiophilic substrate to form a uniform LiF-Mg dual-layered SEI through its irreversible conversion reaction with Li metal.…”
Section: Surface Preteatment Strategiesmentioning
confidence: 99%
“…It was previously demonstrated that the nano/microgeometrical structures yield a greater sensitivity. [ 25–28 ] For example, the hierarchically microstructure‐bioinspired flexible piezoresistive sensor with microdome structure exhibits an ultrahigh sensitivity of 53 kPa −1 . [ 29 ] However, these microstructures are expensive and require complex fabrication procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, sensitivity, working range and stability of sensors depend on the micro/nanostructures that responded to external stimuli and the electromechanical signal conversion capability of constituent materials. 23,27,28 For example, micro/nanostructures like cracks, 29,30 wrinkles, 31,32 pyramids 33,34 and domes 35,36 could be popularly found in flexible pressure sensors which have a positive impact in realizing ultrahigh sensitivity. And sensing functional materials like MXene, Ag/Au/Cu nanowires, graphene are also frequently employed to develop pressure sensors with high sensitivity, 37–40 which are well known that they are much expensive.…”
Section: Introductionmentioning
confidence: 99%